1997
DOI: 10.1074/jbc.272.15.10058
|View full text |Cite
|
Sign up to set email alerts
|

Deletion Analysis of the Large Subunit p140 in Human Replication Factor C Reveals Regions Required for Complex Formation and Replication Activities

Abstract: Replication factor C (RFC) and proliferating cell nuclear antigen (PCNA) are processivity factors for eukaryotic DNA polymerases ␦ and ⑀. RFC contains multiple activities, including its ability to recognize and bind to a DNA primer end and load the ring-shaped PCNA onto DNA in an ATP-dependent reaction. PCNA then tethers the polymerase to the template allowing processive DNA chain elongation. Human RFC consists of five distinct subunits (p140, p40, p38, p37, and p36), and RFC activity can be reconstituted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
145
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(154 citation statements)
references
References 40 publications
8
145
1
Order By: Relevance
“…In addition, the N-terminal mutant of ELG1 would probably also be defective in forming the functional RFC complex. Previous reports showed that the C-terminal regions of the yeast Elg1p protein and the large subunit of the human RFC complex are essential for complex formation with the RFC2 to -5 core subunits (31)(32)(33). These results indicate that intact alternative RFC complex formation is not necessary for ELG1 to down-regulate PCNA monoubiquitination.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, the N-terminal mutant of ELG1 would probably also be defective in forming the functional RFC complex. Previous reports showed that the C-terminal regions of the yeast Elg1p protein and the large subunit of the human RFC complex are essential for complex formation with the RFC2 to -5 core subunits (31)(32)(33). These results indicate that intact alternative RFC complex formation is not necessary for ELG1 to down-regulate PCNA monoubiquitination.…”
Section: Discussionmentioning
confidence: 80%
“…Possible explanations underlying the ATP dependence of the RFC(3/ 4)⅐PCNA complex and ATP-independent RFC(2/3)⅐PCNA complex are presented under "Discussion." We lack the RFC1 subunit in isolation or as a heterodimer with another RFC subunit, but we presume it also forms a major contact to PCNA based on studies of human RFC (25,32). The next few experiments take a different approach to assess the importance of RFC1 in RFC⅐PCNA complex formation.…”
Section: Resultsmentioning
confidence: 99%
“…The studies of this report do not rule out contact between PCNA and RFC2 or 5, as only strongly interacting complexes are observed by the non-equilibrium gel filtration technique used here. Indeed it has been suggested that all five RFC subunits contact PCNA in the human system (32).…”
Section: Resultsmentioning
confidence: 99%
“…The other four RFC subunits, referred to as the small subunits, are in the 36 -40-kDa range: yeast Rfc2(D) (human p37), yeast Rfc3(C) (human p36), yeast Rfc4(B) (human p40), and yeast Rfc5(E) (human p38). The N-terminal region of Rfc1, up to the region of homology to the other RFC subunits, can be deleted in both yeast and human RFC without decreasing RFC clamp loader function with PCNA (10,11). Alternative clamp loaders exist in which Rfc1 is replaced by another protein.…”
mentioning
confidence: 99%